Erosional and depositional contourite features at the transition between the western Scotia Sea and southern South Atlantic Ocean: links with regional water-mass circulation since the Middle Miocene - Pérez, Lara F.; Hernández Molina, F. Javier; Esteban, Federico Damián; Tassone, Alejandro Alberto; Piola, Alberto Ricardo; Maldonado, Andrés; Preu, Benedict; Violante, Roberto Antonio; Lodolo, Emanuele (Geo-Marine Letters)
The aim of the present study was to characterise the morpho-sedimentary features and main stratigraphic stacking pattern off the Tierra del Fuego continental margin, the north-western sector of the Scotia Sea abyssal plain (Yaghan Basin) and the Malvinas/Falkland depression, based on single- and multi-channel seismic profiles. Distinct contourite features were identified within the sedimentary record from the Middle Miocene onwards. Each major drift developed in a water depth range coincident with a particular water mass, contourite terraces on top of some of these drifts being associated with interfaces between water masses. Two major palaeoceanographic changes were identified. One took place in the Middle Miocene with the onset of Antarctic Intermediate Water flow and the enhancement of Circumpolar Deep Water (CDW) flow, coevally with the onset of Weddell Sea Deep Water flow in the Scotia Sea. Another palaeoceanographic change occurred on the abyssal plain of the Yaghan Basin in the Late Miocene as a consequence of the onset of Southeast Pacific Deep Water flow and its complex interaction with the lower branch of the CDW. Interestingly, these two periods of change in bottom currents are coincident with regional tectonic episodes, as well as climate and Antarctic ice sheet oscillations. The results convincingly demonstrate that the identification of contourite features on the present-day seafloor and within the sedimentary record is the key for decoding the circulation of water masses in the past. Nevertheless, further detailed studies, especially the recovery of drill cores, are necessary to establish a more robust chronology of the evolutionary stages at the transition between the western Scotia Sea and the southern South Atlantic Ocean. Fil: Pérez, Lara F. Instituto Andaluz de Ciencias de la Tierra; España. Geological Survey of Denmark and Greenland; Dinamarca Fil: Hernández Molina, F. Javier. Royal Holloway University of London; Reino Unido Fil: Esteban, Federico Damián. Consejo Nacional de ...